Pengaruh Perencanaan Pajak, Beban Pajak Tangguhan dan Kualitas Audit Terhadap Manajemen Laba - Nur Zakiya Anjany Pullah; R. Ery Wibowo A.S; Nurcahyono Nurcahyono (Politeknik Harapan Bersama, 2021)
Abstract: This research was conducted the empirically prove the factors that influence Earnings Management by using the variables tax planning, deffered tax expense and audit quality in banking and insurance companies listed on The Indonesia Stock Exchange in 2015-2019. This type of research is quantitative research with sampling technique using purposive sampling method, namely the selection of samples with criteria determined by the researcher. The method used in this study uses multiple linear regression with the help of the SPSS version 21 program. The results in this study indicate that tax planning and audit quality has a positive and significant effect on earnings management, and deffered tax expense has a negative and not significant effect on earnings management.